Future of Systems Engineering. Issue 1 (29th May 2019) - Watson, Michael D.
ABSTRACT: Systems engineering has evolved as a practice‐based discipline with a matured set of processes covering the life cycle of the system. The engineering basis is however tenuous, as we cannot always ensure the system will be successful. All engineering disciplines start in practice and, over time, evolve with the discovery of the underlying scientific principles that provide a solid foundation for the discipline. Systems engineering is following a similar course, with the recognition that it is also a sociological endeavor integrating, coordinating, and facilitating all the engineering disciplines. As a direct step from the systems engineering heuristics, a set of systems engineering principles emerged that incorporate the engineering basis and the sociological basis and are broader than system principles, that is, principles that define how a system functions. Systems scientists researched the mathematical basis of systems engineering for some time. Recent work has begun to show that mathematical category theory is the basis for defining systems. The future of systems engineering intertwines the scientific/mathematical engineering basis, system modeling advances, and advancements in technological and sociological practices to advance the ability of systems engineering to define systems, shorten design analysis cycles, validate systems, and effectively operate and maintain systems.